Bifidobacterium depletion promotes goiter via gut-thyroid axis: evidence from Mendelian randomization and experimental validation - Liao, Wenyong; Jiang, Yang; Zhang, Jiwen; Wu, Yinghao; Yu, Xue; Chen, Shaohong; Liu, Haiyan; Xiu, Linlin; Zhong, Gansheng (Frontiers in Microbiology, 2025)
BackgroundWhile gut microbiota dysbiosis has been associated with thyroid disorders, its causal role in goiter pathogenesis remains unclear. We aimed to investigate whether specific gut microbial taxa causally influence goiter risk through the short-chain fatty acid (SCFA)-iodine-thyroid axis.MethodsWe performed Mendelian randomization (MR) analysis using gut microbiota genome-wide association study (GWAS) data (MiBioGen consortium, n = 18,340) and goiter GWAS data (FinnGen R10, 10,312 cases/401,869 controls). Experimental validation included: (1) establishing a propylthiouracil (PTU)-induced goiter rat model with 16S rRNA sequencing of fecal samples, (2) targeted SCFAs quantification, (3) thyroid/serum iodine measurement, (4) thyroid hormone assays, and (5) sodium-iodide symporter (NIS) protein expression analysis.ResultsMR analysis identified 10 gut microbial taxa causally associated with goiter risk (all p < 0.05), with Bifidobacterium bifidum showing protective effects (OR = 0.861, 95% CI: 0.764–0.971, p = 0.014). In goiter rats, 16S rRNA sequencing revealed eight differentially abundant microbial taxa including significantly reduced B. bifidum, accompanied by: (1) impairment of two butyrate synthesis pathways, (2) decreased levels of six SCFAs (including butyrate), (3) impaired thyroid iodine uptake, (4) downregulated NIS expression, and (5) thyroid dysfunction [reduced triiodothyronine (T3), thyroxine (T4), free T3 (FT3), free T4 (FT4) with elevated thyroid-stimulating hormone (TSH)] - all measurements showing statistical significance (p < 0.05).ConclusionThis study provides causal evidence that Bifidobacterium depletion may contribute to goiter development through SCFA-mediated impairment of NIS-dependent iodine uptake and thyroid hormone synthesis, highlighting the association of the “gut-thyroid axis” and laying the foundation for early prevention and therapeutic intervention of goiter.